Enhanced absorption of electromagnetic waves in Ti3C2Tx MXene films with segregated polymer inclusions. (8th September 2021) - Iqbal, Aamir; Sambyal, Pradeep; Kwon, Jisung; Han, Meikang; Hong, Junpyo; Kim, Seon Joon; Kim, Myung-Ki; Gogotsi, Yury; Koo, Chong Min
Abstract: MXenes occupy a leading position among materials capable of providing lightweight shielding against electromagnetic interference (EMI) owing to their outstanding metallic conductivity, low density, tunable surface chemistry, and easy solution processing. In this work, we demonstrate that multiple interfaces of segregated structure in MXene composites enhance the absorption of electromagnetic waves. Ti3 C2 T x MXene composite films with segregated polystyrene (PS) inclusions were fabricated via a simple procedure that involves mixing conductive MXene flakes and insulative PS beads in an aqueous medium followed by vacuum filtration and hot pressing. As surface area of multiple interfaces increases, total EMI shielding effectiveness significantly increases at the same volume fraction of PS inclusions. Therefore, the improved shielding efficiency can be attributed to enhanced absorption of electromagnetic waves resulting from strong multiple reflections at internal interfaces of the segregated structure. This work highlights future challenges and provides guidelines toward new structural designs for next-generation shielding materials with tunable electromagnetic wave absorption properties. Graphical abstract: Image 1